The efficiency of some post-emergence herbicides for controlling problematic weeds of lawn areas - R. Gürbüz; H. Alptekin (Труды по прикладной ботанике, генетике и селекции)
This study was carried out to determine the effectiveness of some herbicides on weed species and weed population in the landscape area of Iğdır University Şehit Bülent Yurtseven Campus in 2021. In the study, herbicides with active ingredients, 2,4-D amine, Bromoxynil + MCPA, 2,4-D tri-isopropyl amine salt + Picloram, dicamba + triasulfuron, 2,4-D EHE + florasulam, Halosulfuron-methyl and Fluazifop-p-butyl as well as Bromoxynil + MCPA + dicamba + triasulfuron and 2,4-D amine + Fluazifop-p-butyl herbicide mixtures were used. The percentage effects of the herbicides applied in the study on weed dry weights, weed species, and the percentage effects of herbicides on these weed species were determined according to the 3 counts made at certain intervals for the weed species with a density of 1 weeds/m2 and above in the census.As a result of the study, a total of 14 weed species belonging to 8 families were determined in the trial area. Of these detected weed species, Trifolium  repens L. (5.49 weed/m2),  Cynodon dactylon (L.) Pers. (3.24 weed/m2),  Trifolium  pratense L.  (1.23 weed/m2), Melilotus albus Medik. (1.07 weed/m2) and Convolvulus arvensis L. (1.03 weed/m2), the density of 5 of them was determined as 1 weeds/m2 and above. As a result of the study, the lowest weed dry weights (2.12 g/m2) and the highest percentage effect (94.50%) were obtained in the 2,4-D tri-isopropyl amine salt + Picloram plots. The percentage effects of the herbicides applied in the study on the weed species varied according to the weed species and the herbicides used.